2011
DOI: 10.1007/s00421-011-2007-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of local and systemic aerobic fitness parameters between finswimmers with different athlete grade levels

Abstract: To study the relationship between the local and systemic aerobic fitness parameters, and between the muscle oxygenation and aerobic performance, 16 female finswimmers were recruited and divided into high-level (HL) group and low-level group. Cardiorespiratory function, blood lactate concentration and near infrared spectroscopy muscle oxygenation in the vastus lateralis (VL) were monitored simultaneously during a maximal incremental exercise. We found that the break point (Bp) of the oxygenation index (OI) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…On the other hand, following fatiguing exercise and cuff occlusion, extra oxygen is needed to compensate the oxygen loss in hemoglobin during exercise, and to oxidize lactate generated from anaerobic respiration [49]. This process is termed 'repaying the oxygen debt' [50].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, following fatiguing exercise and cuff occlusion, extra oxygen is needed to compensate the oxygen loss in hemoglobin during exercise, and to oxidize lactate generated from anaerobic respiration [49]. This process is termed 'repaying the oxygen debt' [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, in most studies, ergometer exercises (Ee) traditionally are used to perform what is known as aerobic-type exercise (Sultana et al, 2012; Wang et al, 2012; Wright et al, 2012); and bars, free weights or machines are used to perform traditional anaerobic-type STe (Bloomer 2005; De Sousa et al, 2012; Mukaimoto and Ohno, 2012; Scott et al, 2011). A relevant aspect to be considered is how to match the load and intensity between STe and Ee, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that when combined with global measures of oxygen consumption a multimodality approach of local and systemic physiological monitoring may provide valuable information that could help to more accurately identify athlete response to workload and also inform exercise prescription. 13,14 However, little to no research has focused upon the peripheral aerobic parameters associated with swim exercise, and no research has focused upon muscle oxygenation status in or out of the water.…”
Section: Introductionmentioning
confidence: 99%